An Evidence-Based Systematic Review of Active Hexose Correlated Compound (AHCC) by the Natural Standard Research Collaboration. (1st September 2013) - Ulbricht, Catherine; Brigham, Ashley; Bryan, J. Kathryn; Catapang, Marisa; Chowdary, Divya; Costa, Dawn; Culwell, Samantha; D'Auria, Denise; Giese, Nicole; Iovin, Ramon; Isaac, Richard; Juturu, Vijaya; et al.
ABSTRACT An evidence-based systematic review of active hexose correlated compound (AHCC) by the Natural Standard Research Collaboration consolidates the safety and efficacy data available in the scientific literature using a validated, reproducible grading rationale. This article includes written and statistical analysis of clinical trials, plus a compilation of expert opinion, folkloric precedent, history, pharmacology, kinetics/dynamics, interactions, adverse effects, toxicology, and dosing.